đơn giản biểu thức:tanx + (cosx/(1+sinx))
Giup mik vs
đơn giản biểu thức:tanx +cosx/(1+sinx)
đơn giản biểu thức:tanx +(cosx/(1+sinx))
1) Đơn giản biểu thức : \(A=\frac{\left(sinx+cosx\right)^2-1}{cotx-sinx.cosx}\)
2) Đơn giản biểu thức : \(N=\left(\frac{sinx+tanx}{cosx+1}\right)^2+1\)
\(A=\frac{sin^2x+cos^2x+2sinx.cosx-1}{\frac{cosx}{sinx}-sinx.cosx}=\frac{2sinx^2x.cosx}{cosx-sin^2x.cosx}=\frac{2sin^2x.cosx}{cosx\left(1-sin^2x\right)}\)
\(=\frac{2sin^2x}{1-sin^2x}=\frac{2sin^2x}{cos^2x}=2tan^2x\)
\(N=\left(\frac{sinx+\frac{sinx}{cosx}}{cosx+1}\right)^2+1=\left(\frac{sinx.cosx+sinx}{cosx\left(cosx+1\right)}\right)^2+1\)
\(=\left(\frac{sinx\left(cosx+1\right)}{cosx\left(cosx+1\right)}\right)^2+1=tan^2x+1=\frac{1}{cos^2x}\)
1) Đơn giản biểu thức : \(P=\frac{1-sin^2x.cos^2x}{cos^2x}-cos^2x\)
2)Đơn giản biểu thức : \(M=\frac{2cos^2x-1}{sinx+cosx}\)
\(P=\frac{1-sin^2x.cos^2x}{cos^2x}-cos^2x=\frac{1}{cos^2x}-sin^2x-cos^2x\)
\(=1+tan^2x-\left(sin^2x+cos^2x\right)=1+tan^2x-1=tan^2x\)
\(M=\frac{2cos^2x-1}{sinx+cosx}=\frac{2cos^2x-\left(sin^2x+cos^2x\right)}{sinx+cosx}=\frac{cos^2x-sin^2x}{sinx+cosx}\)
\(\frac{\left(cosx-sinx\right)\left(cosx+sinx\right)}{sinx+cosx}=cosx-sinx\)
giả sử 3.sinx^4-cosx^4=1/2 thì sinx^4+3.cosx^4=
giúp mik vs
giả sử 3.sinx^4-cosx^4=1/2 thì sinx^4+3.cosx^4=
giúp mik vs
giả sử 3.sinx^4-cosx^4=1/2 thì sinx^4+3.cosx^4=
giúp mik vs
Ta có hệ: \(\left\{{}\begin{matrix}3sin^4x-cos^4x=\dfrac{1}{2}\\sin^2x+cos^2x=1\end{matrix}\right.\)
\(\Leftrightarrow\left\{{}\begin{matrix}3\left(1-cos^2x\right)^2-cos^4x=\dfrac{1}{2}\\sin^2x=1-cos^2x\end{matrix}\right.\)
\(\Leftrightarrow\left\{{}\begin{matrix}4cos^4x-12cos^2x+5=0\left(1\right)\\sin^2x=1-cos^2x\left(2\right)\end{matrix}\right.\)
Từ (1) ta có: \(\Leftrightarrow\left[{}\begin{matrix}cos^2x=\dfrac{5}{2}\left(l\right)\\cos^2x=\dfrac{1}{2}\end{matrix}\right.\)
\(\Rightarrow sin^2x=\dfrac{1}{2}\)
\(\Rightarrow sin^4x+3cos^4x=\left(\dfrac{1}{2}\right)^2+3\left(\dfrac{1}{2}\right)^2=1\)
giả sử 3.sinx^4-cosx^4=1/2 thì sinx^4+3.cosx^4=
giúp mik vs
giả sử 3.sinx^4-cosx^4=1/2 thì sinx^4+3.cosx^4=
giúp mik vs